Notes on the Complete Margin of the Second Volume of The Dispute over the Meaning of Czech History - Putna, Martin C. (Dějiny – teorie – kritika, 2007)
Martin Putna's contribution to the discussion distinguishes three ideologically defined positions in consideration of the question of the "meaning of Czech history". These are the Catholic, the Protestant-Masarykian-democratic, and the (post)Marxist. Putna argues that the closest to Havelka's position is the (Protestant)-Masarykian-democratic, and that Havelka tends to consider the Catholic view "from the outside", and with perceptible distance. He considers Havelka's choice of texts by Catholic authors to be not entirely representative and suggests that more characteristic texts could have been chosen in the case of Konstantin Miklík and František Schwarzenberg, for example, and that in the case of Josef Bezdíček the text does not actually belong in the anthology. Conversely he argues that texts by such Catholic authors as Jaroslav Durych, Jan Scheinost, Rudolf Ina Malý or Adolf Kajpr should have been included.